Does witnessing the effects of climate change on glacial landscapes increase pro-environmental behaviour intentions? An empirical study of a last-chance destination. Issue 6 (19th March 2023) - Salim, Emmanuel; Ravanel, Ludovic; Deline, Philip
ABSTRACT: Due To the effects of climate change, tourist locations such as glacial landscapes are increasingly becoming last-chance tourism (LCT) destinations. LCT is paradoxical: although visitors to such locations possess high environmental awareness, their travel generates greenhouse gas emissions that threaten these destinations. However, visiting LCT destinations and observing glacial landscapes threatened by climate change may positively affect pro-environmental behaviour. This article aims to explore how experiencing receding glaciers can influence intentions to adopt pro-environmental behaviour. A quantitative survey of 284 visitors to a major glacier tourism site in France (Montenvers-mer-de-Glace) was caried out to test the influence of landscape, emotions, satisfaction, and LCT-related motivations on intentions to adopt pro-environmental behaviours. The results show that landscapes perceived as symbolic of climate change, LCT motivations, and overall satisfaction positively influenced pro-environmental behaviour intentions. To further encourage such intentions, stakeholders should promote practices based on education and experience.